Haploinsufficiency for AAGAB causes clinically heterogeneous forms of punctate palmoplantar keratoderma. - IRVINE, ALAN (My University, 2012)
Palmoplantar keratodermas (PPKs) are a group of disorders that are diagnostically and therapeutically problematic in dermatogenetics. Punctate PPKs are characterized by circumscribed hyperkeratotic lesions on the palms and soles with considerable heterogeneity. In 18 families with autosomal dominant punctate PPK, we report heterozygous loss-of-function mutations in AAGAB, encoding α- and γ-adaptin-binding protein p34, located at a previously linked locus at 15q22. α- and γ-adaptin-binding protein p34, a cytosolic protein with a Rab-like GTPase domain, was shown to bind both clathrin adaptor protein complexes, indicating a role in membrane trafficking. Ultrastructurally, lesional epidermis showed abnormalities in intracellular vesicle biology. Immunohistochemistry showed hyperproliferation within the punctate lesions. Knockdown of AAGAB in keratinocytes led to increased cell division, which was linked to greatly elevated epidermal growth factor receptor (EGFR) protein expression and tyrosine phosphorylation. We hypothesize that p34 deficiency may impair endocytic recycling of growth factor receptors such as EGFR, leading to increased signaling and cellular proliferation
PUBLISHED
Keywords: Palmoplantar keratodermas (PPKs); Immunology, Inflammation & Infection